Analisis strategi inovasi digital dalam meningkatkan kinerja perbankan syariah di indonesia: Dampak Inovasi Digital terhadap Kinerja Bank Syariah - rizaluddin, m. sofyan (Maliki Interdisciplinary Journal, 2025)
In today's era, the pace of technological development is extremely rapid. This rapid technological development is encouraging financial institutions, including Islamic banks, to transform to increase competitiveness and operational efficiency. Digital innovation is a crucial strategy for strengthening Islamic bank performance through improved services, cost efficiency, and expanding financial inclusion. This article aims to analyze the digital innovation strategies implemented by Islamic banks to improve financial and non-financial performance. This research uses a descriptive qualitative approach through analysis of various scientific journals and recent academic publications. The analysis results indicate that Islamic banks implement several digital innovation strategies, including product and service digitization, strategic partnerships with Islamic fintech companies, strengthening cybersecurity systems, and utilizing big data and artificial intelligence. Digital innovation has been proven to improve operational efficiency, expand market reach, and enhance customer loyalty. However, Islamic banks also face challenges such as limited digital literacy, human resource readiness, and the need to maintain compliance with Islamic principles. Cross-sector collaboration and adaptive regulatory support are needed for digital innovation strategies to be sustainable and provide maximum benefits for the Islamic financial industry.